La bande dessinée à voix haute : introduction - Benoît Glaude; Ian Hague (Comicalités)
This dossier is about comics as sound objects. The collection of articles and interviews examines how comics can be adapted, remediated and/or transformed into aural works. The collection’s scope includes songs, radio dramas, audiobooks, and other aural forms, such as a spoken reading of a comic.